EFFECT OF MULCH AND MIXED CROPPING GRASS - LEGUME AT SALINE SOIL ON GROWTH, FORAGE YIELD AND NUTRITIONAL QUALITY OF GUINEA GRASS - Kusmiyati, F.; Sumarsono, S.; Karno, K.; Pangestu, E. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The research was conducted to evaluate the effect of mulch and mixed cropping grass – legume atsaline soil on growth, forage yield and nutritional quality of guinea grass. Saline soil used in thisresearch was classified into strongly saline soil with low soil fertility. The research was arrranged inrandomized complete block design with 3 blocks. The treatments were : M1 = guinea grassmonoculture, without mulch; M2 = guinea grass monoculture, 3 ton/ha mulch; M3 = guinea grassmonoculture, 6 ton/ha mulch, M4 = mixed cropping grass with Sesbania grandiflora, without mulch;M5 = mixed cropping grass with Sesbania grandiflora, 3 ton/ha mulch; M6 = mixed cropping grass withSesbania grandiflora, 6 ton/ha mulch. Data were analyzed using analysis of variance, then followed byDuncan's Multiple Range Test. The highest soil moisture content was achieved at mixed cropping grasslegumewith 6 ton/ha of mulch. The effect of mulch at saline soil significantly increased plant growth,forage yield and nutritional quality of guinea grass. Application of 3 ton/ha mulch increased plantgrowth, forage yield and nutritional quality of guinea grass. Plant growth, forage yield and nutritionalquality of guinea grass were not affected by monoculture or mixed cropping with Sesbania at saline soil.